2004
DOI: 10.1007/s10162-004-4050-5
|View full text |Cite
|
Sign up to set email alerts
|

Across- and Within-Channel Envelope Interactions in Cochlear Implant Listeners

Abstract: The effects of modulated maskers on detection thresholds of a 50-Hz sinusoidal amplitude modulation (SAM) in a signal carrier were measured in nine cochlear implant (CI) listeners as a function of masker envelope type and for different masker-signal electrode separations. Both signal and masker were 200-ms-long pulse trains, presented concurrently in an interleaved stimulation mode. Masker envelopes were SAM at 20, 50, (0-and p-phase re: the signal modulator), and 125 Hz, as well as noise amplitude modulated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
3
21
4
Order By: Relevance
“…The effect of stimulation mode on MDTs was evaluated in the present experiment to test whether representation of the envelope would be enhanced by a larger spatial spread of excitation or by the change/shift in DR. Chatterjee (2003) showed that channel interaction increased when synchronized envelopes were presented to tonotopically remote electrodes. Modulation detection interference also increases when modulated maskers are presented to tonotopically remote electrode locations (Chatterjee and Oba 2005). In some way, these data imply that amplitude envelope cues might be more salient when presented to a wide region of the cochlea (e.g., BP + 13 and monopolar stimulation modes used in the present study) rather than a restricted region (e.g., BP + 3 in the present study).…”
Section: Discussionsupporting
confidence: 55%
“…The effect of stimulation mode on MDTs was evaluated in the present experiment to test whether representation of the envelope would be enhanced by a larger spatial spread of excitation or by the change/shift in DR. Chatterjee (2003) showed that channel interaction increased when synchronized envelopes were presented to tonotopically remote electrodes. Modulation detection interference also increases when modulated maskers are presented to tonotopically remote electrode locations (Chatterjee and Oba 2005). In some way, these data imply that amplitude envelope cues might be more salient when presented to a wide region of the cochlea (e.g., BP + 13 and monopolar stimulation modes used in the present study) rather than a restricted region (e.g., BP + 3 in the present study).…”
Section: Discussionsupporting
confidence: 55%
“…When more than 1 channel is stimulated simultaneously, one could expect negative effects of channel interaction due to spread of excitation and/or -if the channels are perceptually distinguishable -effects similar to mod- ulation detection interference, which is also found in CI listeners [Chatterjee and Oba, 2004;Richardson et al, 1998]. The results of the current study do not seem to reflect this finding.…”
Section: Methodscontrasting
confidence: 56%
“…Thus, when pulse phase duration is modulated, the same AM depth would result in even smaller loudness increases than those observed in the present study and by McKay and Henshall (2010). Chatterjee (2003) and Chatterjee and Oba (2004) reported on modulation detection interference (MDI) effects in electrical stimulation. The interference observed in those studies caused AM depths to increase by large amounts in order to reach AM detection threshold in many CI listeners.…”
Section: The Listener's Ability To Use Intensity Cuescontrasting
confidence: 48%
“…If levelroving had been used in those studies, the MDI effects would have likely been magnified. Thus, the MDI reported by Chatterjee (2003) and Chatterjee and Oba (2004) was possibly underestimated relative to the true size of the effect.…”
Section: The Listener's Ability To Use Intensity Cuesmentioning
confidence: 98%